Big as life : three tales for spring - Howard, Maureen, 1930- (New York : Viking, 2001)
A collection of stories by American author Maureen Howard featuring such themes as responsibility, loss of faith, innocence, sexuality, ambition and obsession, marriage, art and science, and the natural world.
Booklist starred.
New York Times.
Adult
Keywords: Spring -- Fiction; Short stories; Spring -- Fiction